Exceptional mechanical properties of wire arc additive manufactured Mg-9Gd-3Y-0.5Zr alloy induced by promoted precipitation behavior - Junmin Zhan; Guohua Wu; Xin Tong; Fangzhou Qi; Qiman Wang; Rui Jiang; Youjie Guo; Zhanyong Zhao; Peikang Bai (Journal of Magnesium and Alloys, 2025)
Additive manufactured Mg-RE alloys usually show exceptional mechanical properties, which is mainly attributed to their refined grains in previous studies. Since Mg-RE series are typical age-hardenable alloys, this study focuses on the aging behavior of wire arc additive manufactured Mg-9Gd-3Y-0.5Zr (GW93K) alloy and compares it with the as-cast counterpart, providing a new insight into the strengthening mechanism of additive manufactured alloys. It was revealed that both the refined equiaxed α-Mg grains and small-sized (only 5∼10 nm) β′ precipitates with an extremely high number density (∼2.53 × 104 µm−2) should be considered for the strengthening mechanisms of the deposited alloy. The promoted precipitation behavior is facilitated by the dislocation pile-ups formed under multiple thermal cycles and a high cooling rate during deposition. As a result, the deposited alloy at peak-aged state exhibits better comprehensive properties of UTS=392 MPa and EL=3.3%, which is 19% and 18% higher than that of the cast sample, individually.